Evaluation of carcass traits of Lagunaire, Borgou and Zebu Fulani bulls raised on natural pasture in Benin. , (4): 2012-87 - SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; DAHOUDA, MOHAMADOU; AHOUNOU, G. SERGE; KASSA, S.K.; TOUGAN, P. ULBAD; FAROUGOU, SOUAÏBOU; MENSAH, GUY APOLLINAIRE; SALIFOU, SAHIDOU; CLINQUART, A.; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2012)
In Benin, there is no assessment related to the body composition of native bovine breeds in spite of the requirements of butchers and consumers. This study aimed at evaluating Benin indigenous cattle carcass characteristics raised on pasture and slaughtered in the abattoir of Cotonou-Porto-Novo at 5 years old. Carcass characteristics, carcass conformation, carcass degree of fat cover and rib segment composition were collected on 40 Lagunaire, 71 Borgou and 110 Zebu Fulani bulls. The carcass traits of the Zebu bulls were significantly higher than those of the Borgou bulls (P<0.001) while the lowest performance was obtained in Lagunaire bulls (P<0.001). Heavier carcass, a higher dressing percentage and empty dressing percentage were recorded in bulls slaughtered in the rainy season than those in the dry season (P<0.05). Zebu Fulani carcasses were characterized by their higher dressing percentage, an important rib muscle thickness, a low fat cover and a weak carcass fat percentage while Borgou carcasses were characterized by a high carcass fat percentage and a good carcass conformation. However, Lagunaire carcasses were characterized by a low fat cover and a weak carcass fat percentage, a poor carcass conformation and a high proportion of bone.
Keywords: Carcass; conformation; fat cover; season; breed; bull; Benin